Pengaruh Locus of Control dan Implikasinya Terhadap Berpikir Kreatif Matematika Siswa SMP (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study explores the influence of locus of control on junior high school students’ creative mathematical thinking and its implications for instructional strategies. Using a quantitative approach with a descriptive correlational method, 16 eighth-grade students from various Jakarta schools participated. The research instruments consisted of a questionnaire and a creative thinking test. The Shapiro-Wilk normality test indicated that the data were not normally distributed, prompting the use of the Wilcoxon non-parametric test. The findings revealed a significant relationship between locus of control and students’ creative thinking abilities (p = 0.013 < 0.05). These results highlight the importance of strengthening internal control beliefs to foster creativity in mathematical problem-solving.